The Effect Of Synergetic Teaching Method oj Students' Logical and Mathematical Thinking Abilities on Social Arithmetics Material In Grade VII - Yosi Maria Marito Napitupulu; Lolyta Damora Simbolon; Simon Panjaitan (STABN RADEN WIJAYA WONOGIRI, 2022)
This study aims to determine the effect of the Synergistic Teaching method on students' logical mathematical thinking ability in the Social Arithmetic material of grade VII at SMP Negeri 1 Berampu in the 2025/2026 academic year, and to measure the magnitude of the influence. The research method used is quantitative with a simple linear regression approach. Based on the results of the analysis, the average value of students' logical mathematical thinking ability is 80.5, with the lowest value being 50 and the highest value being 100, which is included in the